2023
DOI: 10.3390/biomedicines11030657
|View full text |Cite
|
Sign up to set email alerts
|

Novel Therapies for the Prevention of Fibrosis in Glaucoma Filtration Surgery

Abstract: Conjunctival fibrosis remains the major impediment to the success of glaucoma filtration surgery. Anti-metabolites remain the gold standard for mitigating post-surgical fibrosis, but they are associated with high complication rates and surgical failure rates. Establishing a more targeted approach to attenuate conjunctival fibrosis may revolutionize the surgical approach to glaucoma. A new strategy is needed to prevent progressive tissue remodeling and formation of a fibrotic scar, subsequently increasing surgi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 188 publications
0
15
0
Order By: Relevance
“…Amniotic Membrane Amniotic membrane transplantation (AMT) has been used as a biological band-aid with known anti-inflammatory and antifibrotic properties. 133,134 Fujishima et al 135 first described its adjunctive use in glaucoma surgery by suturing the AMT graft beneath the scleral flap after MMC application and found acceptable IOP control postoperatively. Several studies have since reported a benefit in IOP control and reduction in medical therapy when AMT is utilized adjunctively with antimetabolites in refractory glaucoma.…”
Section: Inhibitors Of Vascular Endothelial Growth Factor (Vegf)mentioning
confidence: 99%
See 1 more Smart Citation
“…Amniotic Membrane Amniotic membrane transplantation (AMT) has been used as a biological band-aid with known anti-inflammatory and antifibrotic properties. 133,134 Fujishima et al 135 first described its adjunctive use in glaucoma surgery by suturing the AMT graft beneath the scleral flap after MMC application and found acceptable IOP control postoperatively. Several studies have since reported a benefit in IOP control and reduction in medical therapy when AMT is utilized adjunctively with antimetabolites in refractory glaucoma.…”
Section: Inhibitors Of Vascular Endothelial Growth Factor (Vegf)mentioning
confidence: 99%
“…Amniotic membrane transplantation (AMT) has been used as a biological band-aid with known anti-inflammatory and antifibrotic properties 133,134 . Fujishima et al 135 first described its adjunctive use in glaucoma surgery by suturing the AMT graft beneath the scleral flap after MMC application and found acceptable IOP control postoperatively.…”
Section: Introductionmentioning
confidence: 99%
“…The vicious cycle of inflammation and glaucoma is also relevant in canine patients undergoing filtering surgeries with gonioimplants [ 48 ]. Growth of the fibrotic capsule forming around the gonioimplant (bleb fibrosis), ultimately responsible for implant failure and IOP elevation, is believed to be stimulated (at least in part) by the ‘toxic’ inflamed aqueous humor of glaucomatous dogs that is drained in the subconjunctival space around the gonioimplant [ 48 , 49 , 50 ]. Moreover, antiglaucoma medications contribute to the development of subconjunctival fibrosis [ 30 ], further reducing the drainage of aqueous humor via the filtering device.…”
Section: A Self-perpetuating Vicious Cycle Of Inflammation and Glaucomamentioning
confidence: 99%
“…Moreover, antiglaucoma medications contribute to the development of subconjunctival fibrosis [ 30 ], further reducing the drainage of aqueous humor via the filtering device. As such, limiting inflammation appears to be a major factor in the control of bleb fibrosis [ 48 , 49 , 50 ].…”
Section: A Self-perpetuating Vicious Cycle Of Inflammation and Glaucomamentioning
confidence: 99%
“… 5 , 6 Numerous methods such as the use of antimetabolites, application of beta radiation, amniotic membrane implants and so on are conducted to inhibit bleb scarring, yet the overall effect is unsatisfactory. 7 , 8 , 9 Indeed, in the clinical application, complications including bleb leaking, corneal perforation, hypotony keratopathy, endophthalmitis, and maculopathy happen frequently. 10 , 11 , 12 Individuals suffering from glaucoma hope for new safe and effective options.…”
Section: Introductionmentioning
confidence: 99%